2023
DOI: 10.3390/atmos14060949
|View full text |Cite
|
Sign up to set email alerts
|

Ionosphere over Eastern North Atlantic Midlatitudinal Zone during Geomagnetic Storms

Abstract: The ionospheric response at middle latitudes to geomagnetic storms is not yet very well understood. Total electron content (TEC) variations associated with eight strong geomagnetic storms between 2015 and 2022 obtained from GNSS receivers in the eastern area of the North Atlantic (Portuguese continental and insular territory) are studied in an attempt to fill this gap. It was found that for most of the studied geomagnetic storms, TEC variations are synchronous for the longitudinal ranges from 27° W and 9° W. I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…On the other hand, two other locations, Furnas (Azores) and Funchal (Madeira), are at different longitudes (Furnas, difference in longitude of ~16 • ) or latitudes and longitudes (Funchal, differences in latitude of ~6• and longitude of ~7.5 • ). A recent study [32] of TEC variations during geomagnetic storms at these three locations showed that in most cases, TEC variations at the Lisbon area, Azores, and Madeira are very similar, with higher amplitude observed for the southernmost location (Madeira). Furthermore, it seems that the Funchal TEC series shows variability that can be attributed to the effect of the equatorial electrojet (EEJ).…”
Section: Validation Of the Prototype On Different Datasetsmentioning
confidence: 80%
See 1 more Smart Citation
“…On the other hand, two other locations, Furnas (Azores) and Funchal (Madeira), are at different longitudes (Furnas, difference in longitude of ~16 • ) or latitudes and longitudes (Funchal, differences in latitude of ~6• and longitude of ~7.5 • ). A recent study [32] of TEC variations during geomagnetic storms at these three locations showed that in most cases, TEC variations at the Lisbon area, Azores, and Madeira are very similar, with higher amplitude observed for the southernmost location (Madeira). Furthermore, it seems that the Funchal TEC series shows variability that can be attributed to the effect of the equatorial electrojet (EEJ).…”
Section: Validation Of the Prototype On Different Datasetsmentioning
confidence: 80%
“…This can also be deduced from the width of histograms shown in Figure 6. We interpret this difference as the influence (unaccounted by used input SWp) of EEJ and events related to the equatorial ionosphere (as, for example, equatorial plasma bubbles that in some regions and under certain conditions can reach Madeira longitude and latitude [32,33]).…”
Section: Validation Of the Prototype On Different Datasetsmentioning
confidence: 99%